Energy metabolism of the equine cumulus oocyte complex during in vitro maturation - Lewis, N. (Sci Rep, 2020)
Horses are one of the few species, beside humans, in which assisted reproductive technology has important clinical applications. Furthermore, the horse can serve as a valuable model for the study of comparative reproductive biology. Here we present the first comprehensive characterisation of energy metabolism and mitochondrial efficiency in equine cumulus-oocyte complexes (COCs) during in vitro maturation (IVM), as determined using a combination of non-invasive consumption and release assays and mitochondrial function analysis. These data reveal notable species-specific differences in the rate and kinetics of glucose consumption and glycolysis throughout IVM. Approximately 95% of glucose consumed was accounted for by lactate production; however, high concurrent oxygen consumption indicated a comparatively increased role for non-glycolytic oxidative phosphorylation. Up to 38% of equine COC oxygen consumption could be attributed to non-mitochondrial activities and there was a significant loss of spare respiratory capacity over the course of IVM. Notably, our data also revealed that current IVM protocols may be failing to satisfy the metabolic demands of the equine COC. Our findings constitute the first report on mitochondrial efficiency in the equine COC and provide new insight into comparative gamete biology as well as metabolism of the COC during in vitro maturation.